2021
DOI: 10.1002/cam4.3963
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal factors associated with the immunosuppressive tumor microenvironment and melanoma metastasis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…Since miRNAs’ expression information is absent from our dataset, our conclusions cannot include the direct association with the miRNAs. In line with several previous reports that have highlighted the importance of immune function in the process of melanoma metastasis and ICB response [ 52 , 53 , 54 , 55 ], our results show a profound influence of the dysregulation of these non-coding RNAS (ncRNAs) on the activation or inhibition of key anti-tumor immunological processes, such as the Th1, natural-killer cell-signaling, T-cell receptor signaling or the PD-1–PD-L1 cancer immunotherapy pathways. Interestingly, the expression perturbation of the responders was associated with an increasing expression of PD-1 and PD-L1 (CD274).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since miRNAs’ expression information is absent from our dataset, our conclusions cannot include the direct association with the miRNAs. In line with several previous reports that have highlighted the importance of immune function in the process of melanoma metastasis and ICB response [ 52 , 53 , 54 , 55 ], our results show a profound influence of the dysregulation of these non-coding RNAS (ncRNAs) on the activation or inhibition of key anti-tumor immunological processes, such as the Th1, natural-killer cell-signaling, T-cell receptor signaling or the PD-1–PD-L1 cancer immunotherapy pathways. Interestingly, the expression perturbation of the responders was associated with an increasing expression of PD-1 and PD-L1 (CD274).…”
Section: Discussionsupporting
confidence: 92%
“…Two of the main molecules highlighted by the ceRNA network ( Figure 5 a) are TNF and IFNG. Recently, the overexpression of TNF, IFNG and IL2, among other molecules, have been reported as key molecules that may enhance melanoma progression through activating the JAK–STAT signaling pathway [ 55 ]. Moreover, other studies indicate that both TNF and IFNG are directly linked with the high density, T-cell infiltration and cytotoxicity of cytotoxic T-cell (CTL) functions [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two of the main molecules highlighted by the ceRNA network (Figure 5a) are TNF and IFNG. Recently, the overexpression of TNF, IFNG and IL2 among other molecules have been reported as key molecules that may enhance melanoma progression through activating the JAK-STAT signaling Pathway [70]. Moreover, other studies indicate that both TNF and IFNG are directly linked with high density and T cell infiltration and Cytotoxicity of cytotoxic T cells function (CTL) [71].…”
Section: Discussionmentioning
confidence: 99%
“…Two previous integrated analysis studies reported that RBM26-AS1 acts as a ceRNA in high-glucose-induced human retinal endothelial cells ( Cao et al, 2020 ) and pancreatic cancer ( Liu et al, 2020 ). Furthermore, in melanoma, RBM26-AS1 dysregulation has been found in CD4 memory T cells ( Zhang et al, 2021 ). It is noteworthy that the association between these three lncRNAs with ASD has been reported in this study for the first time; therefore, more research is required to confirm our findings.…”
Section: Discussionmentioning
confidence: 99%